HUMAN KINETICS IN XXI CENTURY: CONTRIBUTIONS OF MANUEL SÉRGIO FOR YOUR UNDERSTANDING (Fiep Bulletin - online, 2012)
The text aims to present perspectives of the theory of human kinetics beginning of this century. At firstManuel Sergio text is displayed as a mastermind of epistemology for Physical Education known as HumanKinetics. At a later stage the Science of Human Kinetics (SHM) is presented based on the following pillars: MotorEducation, Sports, Dance, ergomotricity Special Education / Rehabilitation and Circus. By way of final commentsand recommendations the text talks about some contributions from Manuel Sergio theory to understand the placethe body in the University.
Keywords: Physical Education. Human Kinetics. Manuel Sergio